A Comparison of Autism-Specific Training Outcomes for Teachers and Paraeducators. (November 2019) - Bertuccio, Rebecca F.; Runion, Megan C.; Culler, Erica D.; Moeller, Jeremy D.; Hall, Cristin M.
Most students with autism engage in the general education (GE) setting for a majority of the school day. Though there are standards to identify the expectations for educating students with autism in the inclusive classroom, GE teachers and paraeducators report limited knowledge and self-efficacy in supporting students with autism, and both indicate a need for more formal training in autism. In the present study, the authors analyzed GE teachers' and paraeducators' levels of knowledge and self-efficacy prior to and following autism-focused in-service training. Participants attended an informational and a practical training in which knowledge, self-efficacy, and satisfaction were measured. Results for GE teachers and paraeducators followed similar patterns in that knowledge of autism increased significantly, but did not sustain over time. Levels of self-efficacy increased significantly following the practical training. GE teachers demonstrated higher levels of knowledge compared to paraeducators across time, while levels of self-efficacy converged between the two groups. Implications regarding training and professional development are discussed.